Important Features of State Assessment Systems from the Local Perspective Interim Report - Stecher, Brian M.; Barron, Sheila; Borko, Hilda; Wolf, Shelby; National Center for Research on Evaluation, Standards, and Student Testing, Los Angeles, CA. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
This is the first report from a 5-year study of the classroom level effects of state assessment reforms. The first year examines changes in the teaching of writing and mathematics in Kentucky elementary and middle schools as a result of the Kentucky Instructional Results Information System and the Kentucky Education Reform Act (KERA). This report presents a framework for describing the effects of assessment reforms at the classroom level. Eleven features of state assessment reform that are salient at the classroom level are described and the perspectives of classroom teachers and researchers on these features are compared. The list of features should alert researchers to important aspects of assessment reform, and the comparison of the two perspectives should help both groups think more effectively about these issues. These 11 features are: (1) purposes; (2) content; (3) logistics; (4) inclusion and accommodation; (5) accountability; (6) meaningfulness; (7) stability; (8) training and support; (9) classroom practices; (10) performance standards; and (11) commitment. (Contains 1 table and 25 references.) (Author/SLD)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R305B60002.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Classroom Techniques; Educational Assessment; Educational Change; Elementary Secondary Education; Longitudinal Studies; Models; Standards; State Programs; Teaching Methods; Testing Programs; Kentucky Education Reform Act 1990 -- Reform Efforts; Kentucky Instructional Results Information System; Reports, Descriptive